Cost reduction study of automotive part using DFA method headlamp - Farhan, Ab Razak (2010)
The ability to produce new product design with features such as a lower cost, higher quality than the original product is a key factor in meeting the market demand. Design for Assembly (DFA) has been widely used in industry and has produced many successes. Some of the methods known in the DFA industry now are the Boothroyd- Dewhurst DFA method, Hitachi assemblability analysis method (AEM) and the Lucas DFA-Hull method. With these well-known methods, many important changes and developments carried out either manually or through the automatic assembly. The goals of this project are to analyse existing headlamp using Boothroyd-Dewhurst DFA and Hitachi Assemblability Evaluation Method (AEM) in terms of assembly time, assembly cost and assembly efficiency. The headlamp that has been used in this project is a Saga BLM headlamp. The original headlamp and proposed headlamp design have been compared between each other’s and the best result is the proposed design which has the lowest assembly time, lowest assembly cost and highest percentage of design efficiency that is the third proposed design headlamp for each method.